ANALISIS KOLEKTOR PELAT BERGELOMBANG TERHADAP PANAS YANG BERGUNA DAN LAJU PENGERINGAN PADA SOLAR DRYER RUMPUT LAUT DI SUMBAWA - Abdul Malik Karim; Mietra Anggara; Sopyan Ali Rohman; Fadhli Dzil Ikram (Fakultas Teknologi Lingkungan dan Mineral - Universitas Teknologi Sumbawa, 2020)
Seaweed is one of the superior commodities of aquaculture in Kertasari Village, Taliwang District, Sumbawa Barat, Nusa Tenggara Barat, with an area of ??1,550 ha in 2013 with a production of 9,850 tons. Post-harvest handling and processing of seaweed is still conducted traditionally, efficiency and the quality of seaweed produced is low. Long enough drying can affect the growth of microorganisms in seaweed, causing the growth of mold and fungus. The explanation of the problem above makes the writer try to find a solution of the problems faced by seaweed farmers in Kertasari Village, with a maker of seaweed dryers based on Solar Dryer. The solar dryer uses a corrugated plate solar collector with a slope angle of 45o and a zinc plate material with a thickness of 0.4 mm with a conductivity value (k) of 116 W / moC. In addition it uses a clear glass cover with a thickness of 3 mm with a slope of 15o. This tool uses a framework in the form of aluminum, with the tilt angle used can produce a Tout of 70.64 oC and Tin of 56.11 oC.